The correlation of categories of “morale spirit” and “moral psychological state” - Illiuk О. О. (Honor and Law, 2019)
Here have been conducted analyses the correlation categories of the “morale spirit” and “moral psychological state”. It defines essence, content, estimate and sense of morale spirit of personnel. It has been determined the main directions of the personnels achievements and maintenance of a high morale spirit.